An overview of synthetic‐type control charts: Techniques and methodology. (30th May 2019) - Rakitzis, Athanasios C.; Chakraborti, Subhabrata; Shongwe, Sandile C.; Graham, Marien A.; Khoo, Michael Boon Chong
Abstract: In this paper, we provide an overview of a class of control charts called the synthetic charts. Synthetic charts are a combination of a traditional chart (such as a Shewhart, CUSUM, or EWMA chart) and a conforming run‐length ( CRL ) chart. These charts have been considered in order to maintain the simplicity and improve the performance of small and medium‐sized shift detection of the traditional Shewhart charts. We distinguish between different types of synthetic‐type charts currently available in the literature and highlight how each is designed and implemented in practice. More than 100 publications on univariate and multivariate synthetic‐type charts are reviewed here. We end with some concluding remarks and a list of some future research ideas.